HIV care and treatment experiences among female sex workers living with HIV in sub-Saharan Africa: A systematic review. Issue 4 (16th December 2016) - Lancaster, Kathryn E.; Cernigliaro, Dana; Zulliger, Rose; Fleming, Paul F.
Abstract : Female sex workers (FSW) living with HIV in sub-Saharan Africa have poor engagement to HIV care and treatment. Understanding the HIV care and treatment engagement experiences of FSW has important implications for interventions to enhance care and treatment outcomes. We conducted a systematic review to examine the HIV care experiences and determinants of linkage and retention in care, antiretroviral therapy (ART) initiation, and ART adherence and viral suppression among FSW living with HIV in sub-Saharan Africa. The databases PubMed, Embase, Web of Science, SCOPUS, CINAHL, Global Health, Psycinfo, Sociological Abstracts, and Popline were searched for variations of search terms related to sex work and HIV care and treatment among sub-Saharan African populations. Ten peer-reviewed articles published between January 2000 and August 2015 met inclusion criteria and were included in this review. Despite expanded ART access, FSW in sub-Saharan Africa have sub-optimal HIV care and treatment engagement outcomes. Stigma, discrimination, poor nutrition, food insecurity, and substance use were commonly reported and associated with poor linkage to care, retention in care, and ART initiation. Included studies suggest that interventions with FSW should focus on multilevel barriers to engagement in HIV care and treatment and explore the involvement of social support from intimate male partners. Our results emphasise several critical points of intervention for FSW living with HIV, which are urgently needed to enhance linkage to HIV care, retention in care, and treatment initiation, particularly where the HIV prevalence among FSW is greatest.